Association of autoimmune thyroid disease and type 1 diabetes - Gray, Robert Stuart. (The University of Edinburgh, 1983)
Overt autoimmune hyperthyroidism and hypothyroidism were found three times more commonly in insulin-dependent than in non-insulindependent diabetics. Similarly, clinically unrecognised primary autoim¬ mune thyroid failure, as evidenced by elevation of the serum thyrotro¬ phs concentration, was twice as common in insulin-dependent as in noninsulin- dependent diabetics. In contrast to the general insulindependent diabetic population, insulin- dependent diabetics with overt and clinically unrecognised autoimmune thyroid disease were character¬ istically female and middle-aged at the onset of diabetes. Ages at onset of diabetes and of thyroid dysfunction were correlated, suggesting the possibility of a common and coincident pathogenesis. Insulindependent diabetics with coexisting autoimmune thyroid disease showed a higher prevalence of HLA-B8, cytoplasmic and complement-fixing islet cell antibodies than those without thyroid disease. Within the insulin-dependent diabetic population, retinopathy was not related to the coexistence of autoimmune thyroid disease. In diabetics with elevated serum thyrotrophin concentrations but serum total thyroxine concentrations within the normal range, hypothy¬ roidism developed at a rate of 5% per annum in patients with thyroid microsomal antibodies. Thyroid disease was more common in siblings of diabetics with thyroid disease than in those of diabetics without thyroid disease. Insulin-dependent diabetes was more common in siblings of diabetics with a personal or family history of thyroid disease than in those of diabet¬ ics without such a history. In contrast to the younger, male, insulindependent patients, diabetics with coexistent autoimmune thyroid disease showed no seasonal variation in incidence. Thus, the pathogenesis of diabetes, when associated with autoimmune thyroid disease, appears to be dependent upon an inherited predisposition and not on environmental factors.